Effect of Citrus Flavonoids Supplementation on Growth Performance, Oxidative Stress, and Gut Health of Broilers Raised under High Stocking Density - Insawake, Kittisak; Songserm, Thaweesak; Songserm, Ornprapan; Homwong, Nitipong; Plaiboon, Atthawoot; Ruangpanit, Yuwares (Journal of Mahanakorn Veterinary Medicine, 2024)
High stocking density can cause stress which leads to negative effects on broiler health and growth performance. Although antibiotic growth promoters (AGPs) could be used to alleviate these effects, they could raise the risk of antibiotic-resistant pathogens. This citrus flavonoid is a potential as an alternative to AGPs. A total of 1,500 one-day-old male chicks (Ross308) were divided into 5 treatments with 10 replicates including, 1) normal stocking density (NSD, 10 birds/m2), 2) high stocking density (HSD, 15 birds/m2), 3) HSD with 50 ppm Bacitracin (BCT50), 4) HSD with 300 ppm citrus flavonoids (FVN300), and 5) HSD with 400 ppm citrus flavonoids (FVN400). There was no significant different in FI and BW (P >0.05) among dietary treatments in all period of experiment. However, during 11-24 DOA, FCR of HSD was significantly higher than the NSD (P<0.05). The supplementation FVN at both levels showed the positive effect on lowering FCR of NSD birds (P<0.05). At 35 DOA, the level H:L ratio and serum MDA levels of HSD birds were significantly higher than those of NSD birds (P<0.05) were significantly decreased in the supplementation FVN at both levels significantly lower these parameters when compared to that of the HSD (P<0.05). The supplementation of FVN significantly increased jejunal villus height and VH: CD ratio of HSD birds (P<0.01). FVN showed a very promising improvement of oxidative stress status and gut health of broilers.